New Plants for Florida: Lisianthus - Brent Harbaugh; Richard L. Jones; Mary Duryea; Berry J. Treat (EDIS)
Lisianthus (Eustoma grandiflorum) is a relatively new cut flower. Sakata Seed Company was the first to offer lisianthus as a new cut flower in the United States in the early 1980s. Growers and consumers alike were anxious to try lisianthus because it has elegant and beautiful flowers in 15 colors, the flowers have a long vase life, and there are few “blue” flowers available in the cut flower market. This document is part of Circular 1440, a publication of the Florida Agricultural Experiment Station, the Agronomy Department and IFAS Communication Services, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date August 2003. Originally published as a booklet by IFAS Communication Services June 2003.